"Disputes in the Recent History of Argentina: Notions, Accounts and Interpretations on the Last Military Dictatorship (1976-1983) " - Campos, Jorge (Revista de Historia Social y de las Mentalidades, 2024)
The present work takes a look at those notions, stories and interpretations that make of this recent past a conflictive and difficult story to reconstruct, given the diverse approaches and centers of intellectual preoccupation that concern the historiographic production around the last argentine military dictatorship (1976-1983). We will focus on four major issues that have marked the construction of meanings in relation to the recent argentine past: anti-subversive struggle, the application of a neoliberal economic plan, state terrorism and the qualification of genocide; finally, the role of the working class and the mass movement.
Keywords: Recent History; Dictatorship; Terrorism; Genocide